The Evolution of the Black-Scholes Model: A Bibliometric Analysis - Medidjati, Adam; Utama, Wahyudayanto; Heryana, Toni; Hartono, Pierdijono (Journal of Accounting Research, Organization and Economics, 2024)
Objective To investigate the development of the Black-Scholes Model in financial research, identify its key contributors, and map its thematic evolution through a bibliometric analysis.Methodology This study employs bibliometric analysis, a research method that uses bibliographic data to analyze trends, patterns, and the impact of scholarly works in the financial research area. The data was extracted from the Scopus database, processed, and visualized using Microsoft Excel, R-Packages software, and the Biblioshiny Web Interface. The data extraction process was conducted on December 25, 2023, identifying 941 relevant documents, with 719 documents determined to be eligible for the analysis.Results The analysis reveals significant evolution in academic interest in the Black-Scholes Model since its introduction in 1978, with key contributors from the United States and the United Kingdom. Early research (19782000) focused on the theoretical basis of the model, while the period 20012010 marked its increasing relevance in economics. The 20112020 period saw the integration of the model in a wide range of economic applications. The 20212023 period highlights a new research focus on applications in fractional differential equations. The model has become an essential element in modern finance, driving innovation in finance education, policy, and cross-disciplinary applications.Research limitations/implications The study is limited by its reliance on data from the Scopus database, which may not encompass all relevant research. Future research could expand the analysis to include other databases and consider qualitative aspects of the Black-Scholes Model's applications.Novelty/Originality This research underscores the importance of the Black-Scholes Model in the evolution of modern finance and its diverse applications. It makes a significant contribution to the study of economics and finance by providing a comprehensive bibliometric analysis of the model's development, key contributors, and thematic evolution.